Pengaruh Latihan Range Of Motion (ROM) terhadap Peningkatan Kekuatan Otot pada Pasien Stroke - Ariga, Fajar Amanah; Sari, Youlanda (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Stroke is the third leading cause of death after heart and right cancer, patients who survive often suffer from a disability in need of rehabilitation to help restore physical abilities and improve the overall quality of life. Permanent paralysis due to stroke can be prevented by rehabilitative therapy. One rehabilitation therapy that is often used is a motion training program or Range Of Motion (ROM). The aim of this study the effects of exercise Meng etahui Range Of Motion (ROM) to increase muscle strength in patients with stroke at Sundari Hospital Medan. The study design using the method of pre-ek s elf men with One Group pretest-posttest desaing, the sample size of 14 respondents to the technique consecutiv e sampling given ROM exercises with exercise 7 days (1 week) with lat i han 6 times a day . Pe ngumpulan data by using observation sheet statistical test d i use is the Wilcoxon test and magnified by a P value of 0.001, this shows the value of p <α (0:05), it can be concluded that there is significant influence (significant) between workouts Range Of Motion to muscle strength in stroke patients at Sundari Hospital Medan